(untitled) (ENTHYMEMA, 2017)
In this article you find the editorial remarks of this special issue on “Wolfgang Iser. Towards Literary Anthropology”, edited by Laura Lucia Rossi. Alongside introducing the content of the issue, the author reflects on Wolfgang Iser’s influence and legacy and on the perspectives of the Iserian studies, in particular with regard to «literary anthropology».